2016
DOI: 10.1002/lt.24628
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane‐bound G protein–coupled bile acid receptor attenuates liver ischemia/reperfusion injury via the inhibition of toll‐like receptor 4 signaling in mice

Abstract: The plasma membrane-bound G protein-coupled bile acid receptor (TGR5) displays varied levels of expression in different tissues. TGR5-induced liver protection has been demonstrated during several liver diseases, except during ischemia/reperfusion injury (IRI). Male adult wild-type and TGR5 knockout (KO) mice were subjected to liver partial warm ischemia/reperfusion. Hepatic injury was evaluated based on serum alanine aminotransferase and serum aspartate aminotransferase. Liver histological injury and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
(51 reference statements)
3
33
0
Order By: Relevance
“…Here, we studied the function and mechanism of TGR5 in H/R-induced injury in H9C2 and HCM cells. We found that the levels of TGR5 mRNA and protein were significantly increased and peaked after 6 h of reperfusion following Hypoxia for 4 h, which is similar to the studies of Yang et al [13] and Zhuang et al [14] who reported that the level of TGR5 improved in the early stages of reperfusion and peaked at 6 h after reperfusion in the liver and hepatocytes after I/R injury. Besides, our present results demonstrated that overexpressed TRG5 alleviates myocardial I/R-induced apoptosis rate and regulates the levels of apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we studied the function and mechanism of TGR5 in H/R-induced injury in H9C2 and HCM cells. We found that the levels of TGR5 mRNA and protein were significantly increased and peaked after 6 h of reperfusion following Hypoxia for 4 h, which is similar to the studies of Yang et al [13] and Zhuang et al [14] who reported that the level of TGR5 improved in the early stages of reperfusion and peaked at 6 h after reperfusion in the liver and hepatocytes after I/R injury. Besides, our present results demonstrated that overexpressed TRG5 alleviates myocardial I/R-induced apoptosis rate and regulates the levels of apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, studies have shown that TGR5 plays a key role in myocardial adaptability, and activated TGR5 may be a potentially attractive treatment option in cardiac hypertrophy and heart failure [11,12]. At present, reports indicated that that TGR5 alleviates the liver I/R-related inflammation and protects hepatocytes from I/R-related apoptosis [13,14]. However, the role and function of TGR5 in myocardial I/R injury remained poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In liver, TGR5 inhibits the expression of inflammatory mediators in response to NF-κB activation induced by LPS in wild-type (WT), but not TGR5 −/− mice (Wang et al, 2011). Yang et al (2016) reported that during ischemia/reperfusion injury TGR5 inhibited inflammatory response through suppression of the Toll-like receptor 4 (TLR4)-NF-κB pathway. TGR5 activation can also suppress LPS-induced production of cytokines in Kupffer cells and TGR5-overexpressed THP-1 cells (Kawamata et al, 2003; Keitel et al, 2008).…”
Section: Tgr5 and Different Diseasesmentioning
confidence: 99%
“…Indeed, hypoxia activates multiple hypoxia mediators and in turn accelerate or antagonize hepatic damage [1, 2]. A variety of pharmacological interventions have been proposed to alleviate hypoxic injury in the liver, however, there is no promising therapy for the prevention and treatment of hypoxic liver injury yet [3-6]. …”
Section: Introductionmentioning
confidence: 99%